QUANTIFYING THE ENVIRONMENTAL VALUE IN WESTERN COAST OF SEMARANG CITY, CENTRAL JAVA, INDONESIA - Ifdlol Syukri (Graduate School Bogor Agricultural University (SPs IPB), 2016)
Coastal zone in Semarang City is facing climate change impact namely coastal inundation and sea level rise. These area are home to large and growing numbers of residents, visitors, large nursery area for coastal fauna resulting in many economic activities such as fishery, tourism and industrial development. However, the high concentrations of economic activities in the coastal zone contribute to higher potential of degradation of coastal (environmental) resources that drive these economics. This study aims to estimate the monetary value of coastal environment in two selected coastal wetlands such as beaches and estuary. The data collection has been done through non-site surveys and interviews with several respondents. Economic valuation approaches and techniques have been applied to quantify the value of coastal ecosystems including net factor income, hedonic price and contingent choice method. The highest economic contribution of coastal ecosystems was Fishery value accounts at Rp 23,340,352,861, followed by Amenity value at Rp 439,002,861, and Research value in a range Rp 238,868,000 and Rp 492,870,000. While, the lowest environmental value was estimated as Art value at Rp 214,045,150. For the two selected beaches and estuary, the Recreational/Tourism value was estimated at Rp 19,010,974,803, and Rp 1,011,087,200, respectively.Keywords: Economic valuation, coastal ecosystems, climate change impacts, Semarang coastal area.